Care and the afterlives of industrial moralities in post‐industrial northern England. (7th June 2018) - Goodwin‐Hawkins, Bryonny; Dawson, Andrew
Abstract : Building on recent anthropological work on post‐Fordist affect, this article explores comparatively the 'afterlives' of the social organisation of production. In particular, based on comparative ethnography of milling and mining on Northern England, it explores the very different forms of work organisation and their relationships with similarly contrasting moralities of care amongst and for older people.